Wedelia trilobata-derived biochar mitigates chromium toxicity and improves physiological performance in hydroponically grown Chinese cabbage - Qin, Fengyue; Li, Weidong; Dong, Menglu; Yue, Shuangqi; Weng, Guojie; Wang, Mingxuan; Shan, Xinyu; Ahmed, Waqas; Weng, Jiechang; Mehmood, Sajid (Frontiers in Plant Science, 2025)
IntroductionEnsuring future agricultural sustainability requires innovative solutions to alleviate abiotic stress caused by heavy metal(loid) contamination. Chromium (Cr) toxicity is a major abiotic stressor that threatens leafy vegetable productivity and food safety.MethodsThis study investigates the potential of Wedelia trilobata-derived biochar (WBC= 0, 0.1, 0.5, 1, and 3 g L-1) to mitigate Cr-induced abiotic stress (Cr = 50 mg/L, 7 days) in hydroponically grown Chinese cabbage (Brassica rapa). WBC was synthesized, characterized, and applied at varying concentrations in a flow-through hydroponic system.[Results] Results showed that WBC exhibited a strong chromium adsorption capacity. At an application rate of 3 g/L (T5), chromium accumulation in plant shoots and roots was significantly reduced by 97.12% and 97.15%, respectively, compared to the pure chromium treatment group. In the same treatment (T5), the total chlorophyll and carotenoid contents in plant shoots increased by 128.47% and 183.33%, respectively. Additionally, the malondialdehyde (MDA) content decreased by 29.66% in roots and 15.98% in shoots. Hydrogen peroxide (H₂O₂) levels were reduced by 33.95% in roots and 59.22% in shoots. Proline content also declined by 62.85% in roots and 79.78% in shoots. Conversely, the soluble protein content increased by 17.43% in roots and 28.13% in shoots, while soluble sugar levels rose by 78.09% in roots and 502.35% in shoots. At a lower application rate of 1 g/L (T4), plant root and shoot dry weights increased by 92.39% and 71.57%, respectively. Root length and shoot length also improved by 9.82% and 24.93%. Moreover, calcium and magnesium contents in plant shoots significantly increased by 478.99% and 97.86%, respectively.DiscussionWBC application enhanced plant stress tolerance by boosting photosynthetic pigments and antioxidant enzyme activities including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) while reducing oxidative stress indicators such as proline (PRO). Furthermore, WBC improved macro-nutrient uptake, notably increasing levels of N, P, K, Ca, and Mg. These findings highlight WBC as an effective amendment for alleviating heavy metal-induced abiotic stress, promoting healthier plant growth, and enhancing nutrient assimilation. This study offers valuable insights into biochar-mediated stress mitigation, with promising implications for sustainable agriculture and environmental remediation.